A finite element approach to model high-velocity impact on thin woven GFRP plates. (August 2020) - Alonso, L.; Martínez-Hergueta, F.; Garcia-Gonzalez, D.; Navarro, C.; García-Castillo, S.K.; Teixeira-Dias, F.
Highlights: A 3D continuum damage model to predict the ballistic response of GFRP-plates. Failure criterion is split into energetic components by their mechanical nature. An experimental-numerical study is presented on woven E-Glass Fibre/Polyester. The relative roles of failure mechanisms are studied depending on thickness. Abstract: A finite element model to predict the ballistic behaviour of woven GFRP laminates is presented. This finite element model incorporates a new constitutive model based on a continuum damage mechanics approach able to predict the performance of these laminates under high-velocity impacts. The material parameters of the model are identified from the literature and original experiments conducted in this work. The predictive capability of the model is verified against experimental impact tests. Finally, the model is used to analyse the influence of laminate thickness on different energy absorption mechanisms at velocities near the ballistic limit. This analysis allows for the determination of the principal deformation and failure mechanisms governing the perforation process.